2019
DOI: 10.1113/jp278310
|View full text |Cite
|
Sign up to set email alerts
|

Arterial wall shear rate response to reactive hyperaemia is markedly different between young and older humans

Abstract: Key points The vasodilatory response to reactive hyperaemia is impaired with advancing age, but it is unclear whether this is because of an altered wall shear rate (WSR) stimulus or an altered flow‐mediated dilatation (FMD) response. Using new technology that allows detailed WSR measurement, we assessed the WSR–FMD response in healthy older people. Our data show that older people have a markedly altered and diminished WSR response to reactive hyperaemia compared to young people, but reduced WSR alone does not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…47 FMD is largely attenuated in the elderly. [48][49][50][51] Studies have shown that the FMD of the elderly (age>70) is nearly 50% lower than that of the young (age<30). [48][49][50][51] Different from IMT or diameter discussed above, the age-related decrease of FMD is not linear.…”
Section: Carotid Arteriesmentioning
confidence: 99%
See 1 more Smart Citation
“…47 FMD is largely attenuated in the elderly. [48][49][50][51] Studies have shown that the FMD of the elderly (age>70) is nearly 50% lower than that of the young (age<30). [48][49][50][51] Different from IMT or diameter discussed above, the age-related decrease of FMD is not linear.…”
Section: Carotid Arteriesmentioning
confidence: 99%
“…[48][49][50][51] Studies have shown that the FMD of the elderly (age>70) is nearly 50% lower than that of the young (age<30). [48][49][50][51] Different from IMT or diameter discussed above, the age-related decrease of FMD is not linear. The decline in FMD is not much changed in the group with ages 24 to 39 years 15 but becomes pronounced in men above 40 years and women above 45 years of age.…”
Section: Carotid Arteriesmentioning
confidence: 99%
“…Remarkably, with aging, the vasodilator response to reactive hyperaemia decreases, but it is unclear whether this is due to a change in the stimulus wall shear rate (WSR) or an altered response of FMD. Aizawa et al demonstrated, using newer equipment that allows for the accurate assessment of WSR; elderly subjects exhibit a drastically altered and reduced WSR response to reactive hyperaemia compared with younger subjects [103]. Investigations into the relationship between FMD and microvascular abnormalities in SSc have also been conducted.…”
Section: Flow-mediated Dilation and Assessment Of Endothelial Functionmentioning
confidence: 99%